MIBG Therapy for Neuroblastoma: Precision Achieved With Dosimetry, and Concern for False Responders - Rubio, Pedro M.; Galán, Victor; Rodado, Sonia; Plaza, Diego; Martínez, Leopoldo (Frontiers in Medicine, 2020)
Neuroblastoma causes 15% of cancer mortality in children. High risk neuroblastoma has poor prognosis with high mortality and relapse rate despite multimodal treatment. 123-I-meta-iodo-benzyl-guanidine (mIBG) scintigraphy is one of the current standard diagnosis procedures in neuroblastoma . mIBG can also be used therapeutically, labelled with 131-I, as a radiopharmaceutical agent, delivering targeted radiotherapy to tumoral sites. But published data of this strategy show heterogeneous results. One concern is that in most reports the infused activity is only based in body-weight, which could lead to infra or over-treatment depending on inter-patient variability in radiation absorption. Activity adjustment by whole-body dosimetry can be used to homogeneize the treatment. Also, mIBG avid tumors may lose avidness along the treatment. As mIBG is used both for treatment and response evaluation, this could result in undetected progressions in patients with apparent complete response. We present a retrospective single-centre review of neuroblastoma patients who received therapeutic I-131-mIBG, focusing on cases with dosimetry-adjusted activity. Dosimetry allowed for a more precise delivery of radiation, reducing 81.1% of deviation from absorption target of 4 Gray, from 23,4% (±0,936 Gy) to 4,4% (± 0.176 Gy). Patients who showed partial or complete response had better and longer survival. Relapse/progression in non-responders was an early event (within 3 months from treatment). We also present one case of progression with apparent complete response due to loss of MIBG avidness, detected in our series.